Cancer Drug Repositioning by Comparison of Gene Expression in Humans and Axolotl (Ambystoma mexicanum) During Wound Healing - ARĞA, KAZIM YALÇIN (MARY ANN LIEBERT, INC, 2019)
Urodele amphibians such as the axolotl (Ambystoma mexicanum) display a large capacity for tissue regeneration and remarkable resistance to cancer. As a model organism, axolotl thus offers a unique opportunity for cancer research and anticancer drug discovery, not to mention the discerning mechanisms that underpin controlled cellular growth and regeneration versus cancer. To the best of our knowledge, little is known on comparative gene expression changes during regeneration events such as wound healing in axolotl and humans. Using publicly available transcriptomics data and bioinformatics analyses, we examined the differential gene expression signatures in skin wound samples from axolotl and humans after skin biopsy punch injury, in comparison with intact (uninjured) control skin samples. We identified 95 genes exhibiting a reversal expression pattern between humans and axolotl during the wound healing/regeneration period. These genes were significantly associated with collagen biosynthesis, extracellular matrix organization, PI3K-Akt signaling pathway, immune system response, and apoptotic process. Furthermore, this new gene set exhibited high prognostic performance in discriminating the survival risk in skin-related cancers, including melanoma (hazard ratio [HR] = 8.14, p < 10(-30)), oral cancer (HR >100, p < 10(-12)), and head and neck carcinoma (HR = 5.29, p < 10(-30)). Moreover, considering these gene signatures, we repositioned 11 small molecules as potential anticancer drug candidates indicating reversal effects on upregulated human genes and downregulated axolotl genes or mimicking downregulated human genes and upregulated axolotl genes. We anticipate that this study offers new insights on gene signatures bridging regeneration mechanisms with tumorigenesis and cancer drug repositioning.
Keywords: cancer; axolotl; bioinformatics; drug repositioning; regenerative medicine; systems biology; POLY(ADP-RIBOSE) POLYMERASE-1 INHIBITOR; LANGERHANS CELLS; HUMAN SKIN; REGENERATION; RECEPTOR; RADIOSENSITIZATION; OVEREXPRESSION; IDENTIFICATION; TRANSCRIPTOME; BIOMARKERS